Validity and Predictive Accuracy of the Structured Assessment of Protective Factors for Violence Risk in Criminal Forensic Evaluations: A Swiss Cross-Validation Retrospective Study - Abbiati, Milena (Criminal justice and behavior, 2017)
Some actuarial and structured professional judgment (SPJ) risk-assessment instruments have already demonstrated their validity and predictive accuracy in expert criminal forensic evaluations. In contrast, little is known about the effectiveness of instruments identifying protective factors in risk of recidivism prediction. The present study was designed to evaluate the validity and predictive accuracy of the Structured Assessment of Protective Factors for Violence Risk (SAPROF) in 94 violent and sexual violent offenders assessed in a Swiss pretrial criminal forensic context. The SAPROF showed good interrater reliability, and was significantly correlated to predominately dynamic instruments but not to predominately actuarial instruments. However, in terms of predictive accuracy, the SAPROF did not perform as well as expected when compared with other instruments and with previous SAPROF accuracy validation studies. These results have implications for the use of the SAPROF in criminal forensic contexts risk assessment.